Revista época: discurso de classe e atuação política - 1998 a 2006 - Krupiniski, Ricardo (2022)
The aim of this research is to analyze the position of the Brazilian magazine Época during the period from 1998 to 2003, which covers the second mandate of former president Fernando Henrique Cardoso and the first mandate of the also former president Luíz Inácio Lula da Silva. We have attempted to make a historical survey of the birth of Organizações Globo prior to the appearance of Época magazine. In order to better understand the magazine's class discourse, it is essential to analyze the sections Brasil and Economia & Negócios, as well as the issues related to the import (multinationals, financial capital) and export (imperial capital and Brazilian multinationals) of capital. The reflections on this study have as their main theoretical support the ideas of Antonio Gramsci.